Single-cell multiomics connects 3D genome and transcriptome alterations in Alzheimer’s disease - Yang Zhang; Xinyue Lu; Alexander K. Kunisky; Shahul Alam; Junjie Tang; Ruochi Zhang; Shike Wang; Han Zhang; Jude Baroudi; Walid Ichcho; Deyong Jia; Sahar Ghorbanikalateh; et al. (Science, 2026)
Alzheimer’s disease (AD) disrupts brain function through cell type–specific transcriptomic and epigenomic alterations, yet the contribution of three-dimensional (3D) genome organization to AD remains poorly understood. We applied GAGE-seq (genome architecture and gene expression by sequencing) to jointly profile gene expression and 3D chromatin structure in single cells from postmortem brain tissue from AD patients and age-matched individuals without AD, revealing chromatin reorganization linked to cell type–specific dysregulation. Integrations with spatial transcriptomics and chromatin accessibility data uncovered altered niches reflecting genome compartment remodeling and regulatory element reorganization. Hicformer, a deep learning framework, showed that 3D genome features are essential for predicting disease-relevant, cell type–specific gene expression changes. Our results establish higher-order chromatin alterations as a component of AD-associated molecular pathology, providing a multiscale view of transcriptional regulation and 3D genome organization in neurodegeneration.